Effect of birth order on stereoacuity in Chinese preschool children: a cross-sectional study. Issue 10 (12th October 2020) - Han, Shu; Zhang, Xiaohan; Li, Rui; Tong, Haohai; Zhao, Xiaoyan; Wang, Yue; Hao, Qingfeng; Huang, Dan; Zhu, Hui; Zhang, Xiaojun; Liu, Hu
Abstract : Objective: This study aimed to investigate the relationship between birth order and stereoacuity among Chinese children aged 60–72 months. Design: Cross-sectional. Participants: 1342 children with complete data on the questionnaire, stereoacuity and refraction were included. Results: The mean stereoacuity was 53.2±1.7, 56.9±1.9 and 60.9±1.5 s of arc in the first-born group, second-born group and third-born group, respectively. Lower birth order was significantly correlated with better stereoacuity (p=0.036). Third-borns (OR=3.02, p=0.027) were at higher risk of having subnormal stereoacuity compared with first-borns in the multivariate analysis. Conclusion: Later-borns had poorer stereoacuity than first-borns.